Mental health clients’ perspectives on telehealth-based virtual reality therapy - Ong, Triton; Ivanova, Julia; Soni, Hiral; Barrera, Janelle; Cummins, Mollie; Welch, Brandon M.; Bunnell, Brian E. (Frontiers in Virtual Reality, 2025)
There is growing need for better mental health care. It is now possible to combine convenient telehealth with engaging virtual reality towards new opportunities for personalized mental health. The goal of this study was to understand mental health clients’ perspectives on telehealth-based virtual reality therapy. We qualitatively analyzed 17, individual semi-structured interviews of mental health clients about experiences and reactions to exposure therapy over conventional telehealth, virtual reality in general, and telehealth-based virtual reality for mental healthcare. Clients were generally younger adults (M = 29.7 years), female (52.9%, 9/17), non-Hispanic White (88.2%, 15/17), and with varied income (M = $35,671; SD = $30,074; unemployed to $100,000). Clients enjoyed how telehealth made exposure therapy more accessible and comfortable, but could feel unmotivated due to lack of in-person accountability and presence. While none used VR for therapy, most tried VR with positive perceptions of it. All but one client believed telehealth-based VR exposure therapy would be useful, easy, and comfortable. However, many clients were unsure VR would feel realistic. Clients proposed tele-VR for art therapy, avatar-based therapy, and immersive games to build rapport with their therapist. Clients felt tele-VR should address specific needs, and their primary concerns were costs and insurance coverage of VR services. Overall, clients expressed excitement that VR can enhance engagement and personalization of telehealth, if costs are minimized and VR is simple to use. These results provide insights into client needs and suggest key directions to explore immersive telehealth solutions.